Respuesta :
The expression is missing from the question, but here is the given expression which I got from a similar question.
48 + 54 = ___ ´ (8 + 9)
Theleft-hand side of the equation is:
48 + 54 = 102
Now the right-hand side of the equation:
A × (8+9) = Right-hand side
A × (8+9) = 102
Solving for the unknown variable A,
A × 17 = 102
Dividing by 17 on both sides,
A × 17 ÷ 17 = 102 ÷ 17
A × 1 = 6
A = 6
Hence,
48 + 54 = 6 x (8 + 9)
48 + 54 = ___ ´ (8 + 9)
Theleft-hand side of the equation is:
48 + 54 = 102
Now the right-hand side of the equation:
A × (8+9) = Right-hand side
A × (8+9) = 102
Solving for the unknown variable A,
A × 17 = 102
Dividing by 17 on both sides,
A × 17 ÷ 17 = 102 ÷ 17
A × 1 = 6
A = 6
Hence,
48 + 54 = 6 x (8 + 9)
Answer:
The expression is missing from the question, but here is the given expression which I got from a similar question.
48 + 54 = ___ ´ (8 + 9)
Theleft-hand side of the equation is:
48 + 54 = 102
Now the right-hand side of the equation:
A × (8+9) = Right-hand side
A × (8+9) = 102
Solving for the unknown variable A,
A × 17 = 102
Dividing by 17 on both sides,
A × 17 ÷ 17 = 102 ÷ 17
A × 1 = 6
A = 6
Hence,
48 + 54 = 6 x (8 + 9)
Step-by-step explanation: